Primary Esophageal Extra-Gonadal Yolk Sac Tumor Metastasized to the Liver - Abuhelwa, Ziad; Beran, Azizullah; Malhas, Saif-Eddin; Sayeh, Wasef; Sajdeya, Omar; Spencer, Caleb; Assaly, Ragheb (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF To see the formatted meeting abstract.